Learning objectives and environments: How do they affect students’ motivation in English language learning? - Bayu Senjahari; Desfitranita Desfitranita; Martin Kustati (Studies in English Language and Education, 2021)
This study aims to unravel what foremost students learning objectives and expected learning environment as well as to investigate how these two aspects might affect learning motivation. Both quantitative and qualitative research approaches were applied, and the data were collected from questionnaires and interviews. The questionnaire was distributed to 122 students, and the interview session covered eight students. Data from the questionnaire showed that 64.5% of students responded to ‘always’ for future job opportunities, 43.4% for understanding journals, 36.9 for scholarly needs, 36.9% for English as a prestigious language, around 36.2% for becoming a lecturer, 29% for going abroad, and 28.1% for parents’ suggestion. Regarding the learning environments, it was discovered that 67.7% of students responded as ‘strongly agreed’ for teachers should be friendly, 52.9% for opportunities to express opinions, 52.5% for various teaching activities materials, and about 41% for the use of L1 (Indonesian language) in teaching. Moreover, the study showed that learning objectives affect motivation because English was believed for a better future opportunity, for academic requirements such as understanding journals, and for passing standardized test regulation. It was furthermore considered as prestigious and valued for the economy, learned to know its interesting cultures, deemed an attractive language through teachers’ modeling, opened more overseas opportunities as to it is an international language, and parents saw it as a ‘blessing’ to learn. The study also explained that learning environments were influenced by teachers’ personality, teaching methods and materials, and an expectation of a ubiquitous language.